Assessing the influence of retail buyer variables on the buying decision?making process - Vinhas da Silva, R.; Davies, G.; Naudé, P. (European Journal of Marketing, 2002)
Assesses the influence that certain retail buyer characteristics have on how the buyers approach their buying task. By examining five different buyer characteristics and the relative importance that individual buyers place on six different product attributes, draws some pertinent conclusions as to how the buying task is approached. A total of 100 interviews were conducted with UK retail buyers of textiles and clothing in 35 companies, covering 62 separate divisions. The context for each interview was that of a new buy where the options were to source locally or from an international source. A PC?based package (judgmental analysis system, or JAS) was used to assess the importance of six buying criteria derived from the literature and perceived to be relevant in organisational buying. The results confirm what have been largely theoretical ideas of linkages between buyer characteristics and the importance that they place on different criteria during the decision?making process. Clear correlations exist, and these can be explained and supported by the qualitative data gathered during the study.